Mobilidade urbana e entregas ao varejo: proposta de modelo de desempenho da logística de distribuição física - Joao Victor Rodrigues Silva (2013)
This study aims to elucidate the key performance attributes of the activity distribution logistics to retail in urban areas. The process of globalization has caused the densification of cities with most people leaving the countryside to live in an urban environment. In Brazil, as in many other countries, including the most developed, this change has not always been accompanied by planning can facilitate urban mobility. Congestion, pollution, inefficient cargo handling and decreased quality of life are consequences of lack of planning. Remedial measures are taken without have much effect practical. Regarding the logistics of distribution to the retail, logistics and supply chain management emerged as an attempt to solve or at least mitigate the impact of the deterioration in the performance of urban distribution in urban areas. The methodology is divided into two stages. First, interviews were conducted with 15 retailers, in order to draw a scene of urban logistics distribution in the city of Belo Horizonte, as well as their management, at which cards were applied stated preference, which result allowed validate and qualify the importance of performance attributes (cost, 28.45%; service, 27.92%; delivery, 21.76%; reliability, 18.47%, and flexibility, 3.40%) from the perspective of retail. The attribute has not been validated statistically. Validates Flexibility and defined the weights of each, the second step consisted in ranking and selection of performance indicators that comprise the proposed system. The method adopted was the application of a questionnaire to 15 experts in operations management and logistics indicators being defined level (20%) and level B (30%). Thus was formed the system of performance measurement with 11 indicators linked to attributes cost, delivery, service and reliability. After weighted by relative importance of each attribute, came to the proposed system. The use of performance measurement systems offers featured as the ability to measure and control the execution of activities. Thus, the practice of performance measurement provides the implementation of a continuous improvement cycle, being a source of competitive advantage. The strength of the work is the validation and relativize the importance of attributes to the own retail. Finalized the model suggests that this is pioneering, or even serve as a motivation for the development of an indicator for urban mobility that can be measured routinely to assist in the planning of enterprises and governments, as well as inflation.